Anthony Baines Archive - Little, A (University of Oxford, 2024)
A FilemakerPro database in .fmp12 format, containing 12,684 item records (each with an image). The Anthony Baines Archive consists of around 25 boxes/80 folders, containing Baines's notes and other documents from his life, his organology research, and relating to his time as Curator of the Bate Collection of Musical Instruments 1970-80.